Insight into frontal seismogenic zone in the Mentawai locked region from seismic full waveform inversion of ultralong offset streamer data - Qin, Yanfang (2019)
Sumatra subduction zone is one of the most seismically active zones on Earth. After having produced three Mw > 8.4 earthquakes and several Mw > 7.5 earthquakes, including the Mw = 7.8 2010 tsunami earthquake, the northern Mentawai segment is still locked and is capable of generating a great earthquake, possibly a disastrous tsunami. We analyzed ultralong offset seismic reflection data from this locked zone to characterize the nature of the accretionary prism and the plate interface using a combination of traveltime tomography, full waveform inversion, and prestack depth migration. In order to enhance the refractions, we downward extrapolate the streamer data to the seafloor, allowing the refraction arrivals to be observed from near‐zero offset up to far offset, and use a traveltime tomography to determine the background velocity in the upper sediments. Starting from these velocities, we perform a multiscale elastic full waveform inversion to determine the detailed P wave velocity structure of the subsurface. Based on this velocity, we perform a prestack depth migration to obtain seismic image in the depth domain and compute the porosity of the sediments to determine fluid content along faults. Our results show a low‐velocity subduction channel with high porosity at the plate interface that connects the likely active frontal thrusts at the toe of accretionary wedge, suggesting that the frontal section of the prism is seismogenic. We have also observed a low‐velocity layer in the middle of wedge separating old sediments below from new sediments above, defining the roots of bivergent thrust faults up to the seafloor, which can be interpreted as a psudo‐décollement.